Նար-Դոսի ստեղծագործության գնահատության ընթացքը - Պետրոս Դեմիրճյան (ՀՀ ԳԱԱ հրատ.)
Процесс оценки писательской индивидуальности и творчества Нар-Доса (Микаэл Ованисян,1867–1933) в течение более чем одного столетия, можно сказать, никогда не прерывался. С 80–90-х годов XIX века до наших дней были написаны многочисленные статьи, исследования,вошедшие в разные теоретико-аналитические сборники, монографии, изданы собраниясочинений Нар-Доса, неоднократно выходили в свет его отдельные произведения. It can be said that the evaluation process of the individuality and oeuvre of Nar-Dos (Michael Hovhannisyan, 1867–1933) as a writer has never been interrupted for more than one century. There were published numerous articles and studies included in various theoretical-analytical collections, monographs, collections of works, numerous publications of individual works of Nar-Dos from the 80-90ss of the 19th century to the present day.
Keywords: Literature; Language and Literature; PN0080 Criticism